Community Empowerment To Build A Healthy Agricultural Culture Through Garden Living Pharmacy In Parsingguran II Village, Pollung District, Humbang Hasundutan Regency - Sinulingga, Samerdanta; Meutia, Amalia; Pohan, Riko Andika Rahmat; Lubis, Andi Pratama; Kesuma, Sinar Indra (Journal of Community Research and Service, 2023)
The area of Parsingguran II Tourism Village, Pollung District, Humbang Hasundutan Regency has very potential for rural tourism potential to be developed. This village has interesting characteristics, namely nature, culture , and agrotourism . These three potentials are still in the process of being developed by village groups, so this potential must be encouraged and developed following the socio-cultural characteristics of the community. The development of tourism potential based on local wisdom is a strategic effort in developing Parsingguran II Tourism Village. This strategic effort has been accommodated by the USU LPPM in 2021, however, the development of a strategic Tourism Village has not yet produced maximum results in village development. The community empowerment program carried out is to empower agricultural land by building a healthy agricultural culture through a living pharmacy garden to support the development of tourist villages in service locations